Randomised controlled trial of 1% and 5% 5-fluorouracil creams compared with 90% trichloroacetic acid solution for anogenital wart treatment - Anggraini, Ika; Hoemardani, Aida Sd; Nilasari, Hanny; Indriatmi, Wresti (International journal of STD & AIDS, 2020)
To evaluate the efficacy and safety of 1% and 5% 5-fluorouracil (5-FU) creams compared with 90% trichloroacetic acid (TCA) for the treatment of anogenital warts. we conducted a randomised controlled study in 72 subjects allocated to three groups: 1% 5-FU, 90% TCA and 5% 5-FU; 90% TCA was administered once a week, whereas 5-FU cream was applied three times a week. Response to therapy and side-effects were evaluated weekly for seven weeks. Evaluation at week 7 demonstrated that there was no significant difference in the efficacy between 1% 5-FU cream and 90% TCA ( = 0.763) or between 5% 5-FU cream and 90% TCA ( = 0.274). Subjective side-effects with 1% 5-FU were significantly milder than 90% TCA; however, significantly milder objective side-effects were observed only at weeks 2, 6 and 7. The subjective side-effects with 5% 5-FU were also significantly milder than 90% TCA; however, significantly milder objective side-effects were observed only at week 2. 5-FU may become an alternative topical therapy as it offers the benefit of self-application; furthermore, a concentration of 1% 5-FU cream is recommended due to milder side-effects.